Management of Bilingual Class System Program Planning Process at Junior High School - Edy, Sarwo (Jurnal Mamangan, 2024)
This research is motivated by my interest in the use of bilingualism in schools. Since the government implemented the International Standard School Pilot until it was abolished, bilingualism has been implemented in several international schools in Indonesia. The provision of this bilingual program has recently been realized by several international schools in Indonesia who want quality equality with other countries. Here the author will raise the Bilingual Program Planning Process at Bakti Mulya 400 Middle School. The purpose of this study is to determine the management of the bilingual program planning process and academic English skills at Bhakti Mulia 400 Middle School. This research uses a qualitative descriptive analysis method, to collect data. document studies, interviews, and observations were conducted at the institution concerned (Bakti Mulya 400 Middle School). The author conducted interviews with several people involved in the implementation of the bilingual program consisting of school leaders, namely the principal and vice principal, the head of the bilingual program, and the bilingual homeroom teacher. Bilingual class observations include teacher and student activities in the teaching and learning process. From the research that the authors conducted, it can be concluded that the Bilingual Program Planning Process at SMP Bakti Mulya 400 is quite good. This can be seen from the initial planning between school managers and leaders, program development, planning implementation, and evaluation which are carried out systematically and continuously.